The Influence Of Rumah Bumn’s Innovation Strategy On Msme’s Competitiveness: The Quadruple Helix Approach - Vindi Ledys Ihsanda; Wawan Dhewanto (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia’s economic development, contributing significantly to employment, GDP, and innovation. However, they face persistent challenges related to financial access, technological adoption, and market expansion. This study examines the impact of Helix Rumah BUMN’s innovation strategy on MSMEs' competitiveness, with a focus on the moderating role of academia, the Ministry of State-Owned Enterprises (SOEs), and business communities within the Quadruple Helix framework. A mixed-method explanatory sequential design was employed, incorporating quantitative survey data from 260 MSMEs engaged in Rumah BUMN programs and qualitative interviews with MSME owners, facilitators, and policymakers. The results confirm that innovation capability serves as a critical mediator in strengthening MSMEs' competitiveness (β = 0.250, p = 0.005), demonstrating that structured mentorship, financial support, and digital transformation initiatives positively influence market positioning and business sustainability. Government support (β = 0.217, p < 0.001) and business community engagement (β = 0.174, p = 0.002) significantly enhance MSMEs’ innovation-driven competitiveness. However, academic institutions showed an insignificant role (β = 0.029, p = 0.566), suggesting weak university-industry collaboration. The study highlights Helix SOEs and the Ministry of SOEs as key enablers, providing MSMEs with market access, knowledge transfer, and regulatory support. This research underscores the importance of a well-integrated innovation ecosystem, where collaboration among government agencies, industry stakeholders, and research institutions is essential to maximize the impact of innovation strategies. The study recommends strengthening academia-industry partnerships, expanding government-backed incentives, and fostering peer learning through business communities to enhance MSMEs' innovation potential and long-term competitiveness. Future research should explore industry-specific innovation strategies, longitudinal MSME innovation progress, and the role of emerging technologies such as AI, blockchain, and IoT in enhancing MSME growth and sustainability.